Further studies in rat models of neural disinhibition: behavioural, in vivo electrophysiological, and translational imaging studies - Loayza, Joanna (2023)
Neural disinhibition, i.e., reduced inhibitory GABA transmission, has been implicated in various neuropsychiatric disorders. In particular, GABAergic abnormalities in the hippocampus and the striatum have been associated with schizophrenia and Tourette Syndrome, respectively. Regional neural disinhibition may affect behaviour by disrupting regional neural function and by causing changes in projection sites of the disinhibited region. In schizophrenia, one of such projection sites is the septum and in Tourette Syndrome the motor cortex. To further examine the impact of regional disinhibition (ventral hippocampus or anterior dorsal striatum), we combined intra-cerebral microinfusions of a GABA-A receptor antagonist (picrotoxin) with translational neural imaging (MRS, rsFC MRI), electrophysiological measurements and behavioural methods (locomotor activity and prepulse inhibition) in Lister hooded rats.